Analisis Juridis terhadap Disparitas Putusan Hakim dalam Tindak Pidana Transaksi Elektronik dan Pencucian Uang (Studi Putusan Nomor :1240/Pid.Sus/2022/PN. Tng dan Putusan Nomor: 576/ Pid,Sus/2022/PN. Blb.) - Donald, Henry Lbn Toruan; ., Djamilus; Rini, Nicken Sarwo; Fathony, Ahmad (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
This article focuses on the crime of electronic transactions and money laundering. This focus was motivated by reports from victims of fraud by Indra Kenz and Doni Salman via videos circulating on social media regarding the investment business. This uses the Binomo and Quotex applications. During the examination at the Tangerang and Bale District Courts, Bandung, there was a disparity in the sentences imposed by the judges in decision Number: 1240/Pid.Sus/2022/PN.Tng and Decision Number: 576/Pid,Sus/2022/PN.Blb. Indra was sentenced to 6 years and Doni to 4 years. Based on this, this article wants to analyze the reasons that the judge considered in deciding the criminal case of electronic transactions and money laundering for the two perpetrators with different sentences for the two perpetrators. This is because the criminal acts committed by the two perpetrators have similarities. This research uses a normative juridical method with a case approach. Sources of legal research materials used consist of judge's decisions, cases to be analyzed, legislation, books (literature) and scientific journals related to writings and data from news articles. The data collection procedure was carried out by searching data on the internet related to the writing topic. All data collected will be compiled and analyzed using theory or expert opinion. Then, this theory is linked to the reasons or legal considerations (ratio decidendi) used by the judge in making his decision. This study concluded that the disparity in sentences imposed on the two perpetrators was due to the lack of clear regulations prohibiting binary option trading affiliates. Apart from that, there are differences in regulations regarding the spread of fake news that harm consumers in the ITE Law and the Consumer Protection Law.